2012
DOI: 10.1074/jbc.m112.359638
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Analysis of Niclosamide Reveals Potential Role for Cytoplasmic pH in Control of Mammalian Target of Rapamycin Complex 1 (mTORC1) Signaling

Abstract: Background: mTORC1 is dysregulated in human disease, and there is an interest in the development of mTORC1 inhibitors. Niclosamide inhibits mTORC1 signaling, but its mode of action remains unclear. Results: Niclosamide extrudes protons from lysosomes, thus lowering cytoplasmic pH and inhibiting mTORC1 signaling. Conclusion: Cytoplasmic acidification inhibits mTORC1 signaling. Significance: Our findings may aid the design of niclosamide-based anticancer therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
124
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 95 publications
12
124
1
1
Order By: Relevance
“…Niclosamide was able to suppress mTORC1 in TSC2-deficient cells where MTORC1 activity was elevated (5), suggesting that it acted on a different pathway. In addition, it had been proposed that the increased cytosolic acidification was responsible for MTORC1 inhibition although how this could be achieved is not known (6). Our data reported here would support an alternative model that MTORC1 inhibition is caused by lysosomal dysfunction, which affects the v-ATPase-LAMTOR-RAG signaling pathway.…”
Section: Niclosamide Has Dual Effects On Autophagy Induction Andsupporting
confidence: 59%
“…Niclosamide was able to suppress mTORC1 in TSC2-deficient cells where MTORC1 activity was elevated (5), suggesting that it acted on a different pathway. In addition, it had been proposed that the increased cytosolic acidification was responsible for MTORC1 inhibition although how this could be achieved is not known (6). Our data reported here would support an alternative model that MTORC1 inhibition is caused by lysosomal dysfunction, which affects the v-ATPase-LAMTOR-RAG signaling pathway.…”
Section: Niclosamide Has Dual Effects On Autophagy Induction Andsupporting
confidence: 59%
“…It has previously been shown that mTORC1 activity can be inhibited by extracellular acidosis and that this can be dependent or independent of TSC1/2 (5,29). Here we have demonstrated that the intrinsic kinase activity of mTORC1 is itself decreased at acidic pH.…”
Section: Discussionsupporting
confidence: 58%
“…Previous data showed that eEF2 phosphorylation increases when mouse liver extract is incubated in acidified HEPES-KOH buffer and that the activity of recombinant eEF2K kinase is enhanced by acidic pH in vitro (19). However, it was unknown if acidic cytosolic pH increases endogenous eEF2K activity in cells directly or indirectly, via upstream signaling events, e.g., extracellular acidosis can inhibit mTORC1 signaling, and this is mainly TSC2 dependent (5,29). To study this, we cultured HEK293 cells in acid-buffered growth medium for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of mTOR by rapamycin or other signaling pathways is known to stimulate autophagy (53,56) and it has been recently reported that mTOR may be regulated by pH (57). While finalizing this study, an interesting study reported that niclosamide, an autophagy inducing drug causes cytosolic acidification and mTOR inhibition (58).…”
Section: Human Melanoma Cells Survive and Proliferate Also At Verymentioning
confidence: 80%